Molecular Detection of Cryptosporidium parvum by Specific Gene (Heat Shock Protein) in Children at Babylon Center - Hayam Khalis Al-Masoudi; Ola Abdallah Mahdi Dahash (Medical Journal of Babylon)
Background: Cryptosporidium is a diarrhea-causing single-celled parasite that infects the gastrointestinal tract of humans, livestock, birds, and wildlife populations. Objectives: Molecular detection of C. parvum by specific genes in children. Materials and Methods: A total of 300 stool samples were collected from patients aged 17 days to 10 years, (26 females and 49 males) and were represented using a specific gene [Heat shock protein gene (HSP70)] for the diagnosis of C. parvum. Results: The results indicated that from 300 stool samples, 75 (25%) were found to be positive for C. parvum. Additionally, polymerase chain reaction product analysis of the HSP70 gene in C. parvum reported that fifty of the 75 (66.66%) samples observed carried the HSP70. Also, the results indicated that the highest infection rate was recorded in patients of the 17-day age group (27, 36%, and the lowest rate was recorded in the patients of the 9–10 year age group (2, 2.7%) with a significant value. According to gender, the results indicated that the highest percentage was found in males (65.3%), and the lowest percentage was found in females (34.7%). Additionally, the highest infection rate was found in rural areas (62.5%), while the lowest infection was found in urban areas (37.5%). Conclusion: HSP70 could be a good diagnostic tool for the detection of C. parvum among pediatric patients as well as for the monitoring of water resources, in which low concentrations of parasites are usually observed.